DEVELOPING EXTENSIVE READING THROUGH JIGSAW TECHNIQUE - Mohamad Mansur (Journal of English Language and Literature (JELL), 2019)
The purpose of this research is to find out the effectiveness of developing extensive reading through jigsaw technique students of a university in East Jakarta. The method used in this study was qualitative applying the four stages in reading Tales of Terror book. The result shows that each student could answer the comprehension questions with the average score is 86. The students’ achievement in reading comprehension of extensive reading by using jigsaw technique is quite good. The presentation stage shows that most students are able to deliver their understanding of the Tales of Terror book in a very systematic and clear explanation. Referring to the result of the presentation, the writer concluded that jigsaw technique is effective and applicable for the students of university.